Synthesis and Performances of Fatty Alcohol Polyoxyethylene Ether Sulfonate - Yan, Lu; Ping, Fan; Da-shan, Lu (Recent Innovations in Chemical Engineering, 2019)
Background: Fatty alcohol polyoxyethylene ether sulfonate (AESO) was synthesized by the following two steps reactions: fatty alcohol polyoxyethylene ether 5 (AEO-5) reacted with metallic sodium to form sodium alkoxide, then in toluene solvent, the sodium alkoxide reacted with 2-chloroethyl sulfonate sodium to form AESO. Methodology: The reaction factors, such as temperature, reaction time and reactant ratio, which effect on the product yield were discussed. The products were characterized by Fourier Transform Infrared (FTIR) spectra in order to examine the aim of the product synthesized. The AESO performances including thermal stability, salt resistance, emulsifying and surface properties were studied. Results: The results show that the optimum conditions of AESO synthesis are as follows: the reaction temperature is 64oC, the reaction time is 5h, the molar ratio of chloroethyl sulfonate sodium and sodium alkoxide is 1.2:1. In the above reaction conditions, the AESO has the highest yield, which is 74.43% and its purity is 89.25%. AESO’s surface properties, thermal stability, and salt resistance are much better than that of fatty alcohol polyoxyethylene ether sulfate (AES). The AESO presents the best emulsifying performance at the concentration of 1250mg/L. Conclusion: The solubility of AES and AESO are all increased due to the EO groups’ existence and their hard water resistances are better than that of lauryl sodium sulfate. The foamability test shows that AESO has the best foaming ability at the concentration of 1480mg/L, which decreases with the increase of the Ca2+ concentration, but the foam stability increases. It can be seen that AESO has favorable resistance to high temperature and high salinity.
Keywords: Alcohol Polyoxyethylene Ether Sulfonate (AESO)